Vasodilator effects of sulforaphane in cerebral circulation: A critical role of endogenously produced hydrogen sulfide and arteriolar smooth muscle K(ATP) and BK channels in the brain - Parfenova, Helena (J Cereb Blood Flow Metab, 2019)
We investigated the effects of sulforaphane (SFN), an isothiocyanate from cruciferous vegetables, in the regulation of cerebral blood flow using cranial windows in newborn pigs. SFN administered topically (10 µM–1 mM) or systemically (0.4 mg/kg ip) caused immediate and sustained dilation of pial arterioles concomitantly with elevated H(2)S in periarachnoid cortical cerebrospinal fluid. H(2)S is a potent vasodilator of cerebral arterioles. SFN is not a H(2)S donor but it acts via stimulating H(2)S generation in the brain catalyzed by cystathionine γ-lyase (CSE) and cystathionine β-synthase (CBS). CSE/CBS inhibitors propargylglycine, β-cyano-L-alanine, and aminooxyacetic acid blocked brain H(2)S generation and cerebral vasodilation caused by SFN. The SFN-elicited vasodilation requires activation of potassium channels in cerebral arterioles. The inhibitors of K(ATP) and BK channels glibenclamide, paxilline, and iberiotoxin blocked the vasodilator effects of topical and systemic SFN, supporting the concept that H(2)S is the mediator of the vasodilator properties of SFN in cerebral circulation. Overall, we provide first evidence that SFN is a brain permeable compound that increases cerebral blood flow via a non-genomic mechanism that is mediated via activation of CSE/CBS-catalyzed H(2)S formation in neurovascular cells followed by H(2)S-induced activation of K(ATP) and BK channels in arteriolar smooth muscle.